Back from the brink : saving some of the world's rarest animals - Smith, Malcolm, 1949 March 11- (Whittles Publishing, 2015)
'Back from the Brink' is an antidote to a world that seems full of stories of wildlife doom and gloom. Amongst all the loss of habitat and the animals and plants that are in spiralling decline, it's easy to forget that there are a huge number of positive stories too; animals threatened with extinction, such as the gigantic European Bison - extinct in the wild - having their fortunes reversed and their futures secured.